Postactivation potentiation effect of heavy sled towing on subsequent sprints - Williams, J. J.; Heron, R. L.; Spradley, B.; Saracino, P. (The Journal of Strength and Conditioning Research, 2021)
Recent research supports heavy sled towing as a tool used to improve subsequent sprints as part of postactivation potentiation (PAP) protocols. The purpose of this study was to examine the effect of heavy sled towing using a velocity decrement (Vdec) on subsequent unloaded sprinting in high school football (soccer) athletes sprinting on artificial turf. A sled load equating to a 40-50% Vdec range was used (66-70% body mass). Fifteen (n = 9 boys and n = 6 girls) high school football players volunteered for this study. The sled-towing intervention consisted of a dynamic warm-up, 3 submaximal sprint efforts (50, 75, and 95%), and 3 maximum speed 15-m sled sprints, separated by 2-minute rests, of which the fastest time was recorded for analysis. Peak preintervention 15-m baseline sprint times were compared with peak post sled-towing 15-m sprint times using a paired samples t-test. Thirteen of 15 athletes ran faster peak post sled-towing sprint times than peak preintervention baseline sprint times (9 boys and 4 girls). On average, peak post sled-towing sprint times (2.60 ± 0.10 seconds) were 0.10 seconds faster (p < 0.0001; Cohen's d = 0.92) than peak preintervention baseline sprint times (2.70 ± 0.09 seconds). This research established that sled-towing protocols using loads corresponding to Vdec of 40-50% significantly improved subsequent sprints in high school football (soccer) athletes running on artificial turf.